Perlindungan Hukum Terhadap Pekerja Akibat Pelanggaran Pemberian Tunjangan Hari Raya Keagamaan pada Masa Pandemi Covid-19 - Ida Ayu Vera Wirya Paramita; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
Currently, various countries around the world are busy with activities to combat the transmission of the Covid-19 virus pandemic, especially in Indonesia, several companies engaged in industry and tourism in Indonesia in terms of providing holiday allowances (THR) are currently considered very burdensome for companies and businesses. implementation is still far from expectations. The purposes of this study are to examine the legal arrangements for the provision of religious holiday allowances to workers during the Covid-19 pandemic and legal protection for workers due to violations of the provision of religious holiday allowances during the Covid-19 pandemic. This research is a normative legal research with a conceptual approach and legislation. The technique of collecting legal materials is done by using library techniques. Sources of legal materials used in the form of primary and secondary legal sources. The data analysis technique was carried out qualitatively and presented in descriptive form. The results of the study reveal that legal arrangements regarding the provision of religious holiday allowances for workers in companies during the Covid-19 pandemic are regulated in Article 2 of the Regulation of the Minister of Manpower No. 6 of 2016 and strengthened implementing regulations through the Minister of Manpower Decree No. M/6/HK.04/IV/2021 2021 that the provision of religious holiday allowances to workers in the Covid-19 situation will continue to be carried out.